DsbA-L activates TGF-β1/SMAD3 signaling and M2 macrophage polarization by stimulating AKT1 and NLRP3 to promote pulmonary fibrosis - Juan Wang; Zhenkun Xia; Bei Qing; Ying Chen; Linguo Gu; Hongzuo Chen; Zhenglian Ge; Yunchang Yuan (Molecular Medicine)
Abstract Background Pulmonary fibrosis (PF) is a progressive and difficult-to-heal lung disease that poses a significant threat to human life and health. This study aimed to investigate the potential pathological mechanisms of PF and to identify new avenues for the treatment of PF. Methods Clinical samples were collected to assess the effect of disulfide-bond A oxidoreductase-like protein (DsbA-L) on PF. TGF-β1-induced MLE-12 cell model and bleomycin (BLM)-induced mice model were established. Changes in physiological morphology and fibrosis were observed in the lung tissues. The degree of apoptosis and the mitochondrial function was analyzed. The expression of relative cytokines was examined. The CD68+/CD206+ ratio was determined to indicate M2 macrophage polarization. Results The expression of DsbA-L was upregulated in patients with PF and PF-like models. In vitro, DsbA-L overexpression exacerbated TGF-β1-induced the deposition of extracellular matrix (ECM), apoptosis, inflammation, and mitochondrial damage, whereas DsbA-L silencing exerted the opposite effects. DsbA-L silencing inhibited the activation of AKT1, NLRP3, and SMAD3 by TGF-β1. MLE-12 cells silencing DsbA-L limited the polarization of RAW264.7 cells towards the M2 phenotype. AKT1 agonist or NLRP3 agonist reversed the role of DsbA-L silencing in inhibiting the TGF-β1/SMAD3 pathway and M2 macrophage polarization. In vivo, DsbA-L knockout protected mice from PF-like pathological damage caused by BLM. Conclusion DsbA-L exhibited a significant profibrotic effect in lung epithelial cells and mice, which increased the levels of AKT1 and NLRP3 to activate the TGF-β1/SMAD3 pathway and M2 macrophage polarization. These findings could shed light on new clues for comprehension and treatment of PF.